Apakah perselingkuhan daring berkaitan dengan penonaktifan moralnya? - Savitri, Setiawati Intan; Dimarsha, Kyrei Vixy Chika (Jurnal Psikologi Sosial, 2024)
Abstract— Infidelity is a behavior that is considered by society to be immoral, yet it is widely practiced. How the cognitive process in the immoral behavior of infidelity, especially online infidelity in the context of dating relations, is still little studied. This study aims to examine the relationship between moral disengagement and online infidelity behavior in dating relationships. Participants (N = 157, M-age = 21.3) in this study were young adults who had been or were currently dating in Jadebotabek. The method used was descriptive correlation. Measures used were the Internet Infidelity Questionnaire and Infidelity Moral Disengagement measuring instruments, which were adapted to the context of dating relationships in Indonesia. The results showed that there is a significant positive relationship between the cognitive process of moral disengagement and attitude toward online infidelity in individuals who are in a dating relationship. Attitude toward Internet infidelity in women is higher than inmen, while moral disengagement in men is higher than in women. Attitudes toward Internet infidelity are also determined by the length of dating relationships. Keywords: Internet infidelity; Moral disengagement; Dating; Young-adult Abstrak— Perselingkuhan adalah perilaku yang secara social dianggap immoral, namun banyak dilakukan. Bagaimana proses kognitif dalam perilaku immoral perselingkuhan khususnya perselingkuhan daring dalam konteks hubungan berpacaran, masih jarang dilakukan. Penelitian ini bertujuan untuk melihat hubungan moral disengagement dengan perilaku perselingkuhan daring dalam hubungan berpacaran. Partisipan (N = 157, M-usia = 21.3) dalam penelitian ini adalah dewasa muda yang pernah atau sedang berpacaran di Jadebotabek. Metode yang digunakan adalah deskriptif korelasional. Pengukuran menggunakan alat ukur Internet Infidelity Questionnaire dan Infidelity Moral Disengagement yang ditrans-adaptasi sesuai konteks hubungan pacaran dalam bahasa Indonesia. Hasil penelitian menunjukkan terdapat hubungan yang positif signifikan antara proses kognitif moral disengagement dengan sikap terhadap perselingkuhan daring pada individu yang berpacaran. Sikap terhadap Internet infidelity pada perempuan lebih tinggi daripada laki-laki sedangkan moral disengagement pada laki-laki lebih tinggi daripada perempuan. Sikap terhadap internet infidelity juga ditentukan oleh lamanya berpacaran.